2013
DOI: 10.1007/s00018-013-1267-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes to cellular water and element content induced by nucleolar stress: investigation by a cryo-correlative nano-imaging approach

Abstract: The cell is a crowded volume, with estimated mean mass percentage of macromolecules and of water ranging from 7.5 to 45 and 55 to 92.5 %, respectively. However, the concentrations of macromolecules and water at the nanoscale within the various cell compartments are unknown. We recently developed a new approach, correlative cryo-analytical scanning transmission electron microscopy, for mapping the quantity of water within compartments previously shown to display GFP-tagged protein fluorescence on the same ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 55 publications
3
29
0
Order By: Relevance
“…The composition adopted here gives an attenuation length of 5.24 mm at 520 eV or a LAC of 0.19 mm À1 . This LAC value is at the lower end of that found within cells by Do et al (2015) and the water content (91% by mass) is also at the higher end of that found for cytosol in cells (Nolin et al, 2013). This gives partial support to the adoption of this composition as a 'background' against which the contrast of other cellular objects can be calculated.…”
Section: Cytsolsupporting
confidence: 49%
See 1 more Smart Citation
“…The composition adopted here gives an attenuation length of 5.24 mm at 520 eV or a LAC of 0.19 mm À1 . This LAC value is at the lower end of that found within cells by Do et al (2015) and the water content (91% by mass) is also at the higher end of that found for cytosol in cells (Nolin et al, 2013). This gives partial support to the adoption of this composition as a 'background' against which the contrast of other cellular objects can be calculated.…”
Section: Cytsolsupporting
confidence: 49%
“…Measured linear absorption coefficients (LAC) are available for some objects seen by full-field X-ray microscopy (Do et al, 2015;Le Gros et al, 2016;Weiss et al, 2000), water content and atomic compositions from scanning electron microscopy (Nolin et al, 2012(Nolin et al, , 2013 and density values from ptychography (Diaz et al, 2015(Diaz et al, , 2016Bartels et al, 2012). These techniques have different resolutions and do not always give values which agree between the techniques, perhaps because a larger amount of water is included for the lower resolution techniques.…”
Section: The Atomic Composition and Density Of Cellular Componentsmentioning
confidence: 99%
“…25 Because extracellular ATP is detected at plasma membrane-localized P2X 7 receptors resulting in cytosolic potassium efflux, we sought to determine whether the mitochondrial potassium pool was mobilized by macrophage purinergic signaling. We used KS6 and co-localized the signal with MitoTracker Green FM to observe the kinetics of mitochondrial potassium in live J774A.1 cells (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the relatively well-defined components of a typical in vitro biochemical experiment, the cellular nucleus contains hundreds of millions of DNA base pairs (in metazoan genomes), as well as RNA, histones and countless nonhistone proteins. The overall concentration of macromolecules in the nucleus is estimated to be between 100 and 400 mg/ml [112, 113]. Within this crowded nucleoplasm [114], TFs somehow bind specific DNA sites and regulate gene expression.…”
Section: From In Vitro To In Vivo Transcription Factor-dna Interactionsmentioning
confidence: 99%